ASSESSMENT AND TECHNICAL CONSTRAINT IDENTIFICATION OF SMALLHOLDER IRRIGATION PUMP IN ARSI AND EAST SHEWA ZONE, OROMIA - Bayan Ahmed; Tilaye, Asnake (International Journal of Engineering Science Technologies, 2024)
Efficient irrigation begins with properly installed and maintained pumps, motors, and engines. For this, the study was conducted on potential irrigation pump users of the Arsi and East Shewa zones with the objective of identifying the technical constraints of smallholder irrigation pump users. Doddota from Arsi and Dugda and Bora woreda from the East Shewa zone were selected. 211 samples size from 2321 pump users were used for data collection. The constraints listed by respondents, like pump damage, pump cost, long priming, and fuel, were the most common bottlenecks in pump irrigation schemes. Pump damage was positively correlation with use of un-recommended suction and delivery head, age of pump, long priming time and continues operation time but negatively correlation with pump maintenance, experience in irrigation farming and educational level of the household. Long priming and fuel consumption was positively (+Ve) correlation with use of un-recommended suction and delivery head, age of pump, operation time and pump size. From the existing pump type respondent responses, KAMA pumps were highly available on the market, vulnerable to damage, and had sufficient spare parts with values of 60.66, 64.45 and 44.08%, respectively. The lowest were Cushion their values were 1.42%, 3.32% and 3.78%, respectively. The respondents also reply, due to absence of governmental pump maintaining organization, cost of maintenance at local and private garage were very expensive (68.25%) and expensive (26.07%). This makes another problem on small holder irrigation pump. Therefore, it is recommended to government to add pump maintaining structure at engineering center which serves’ closely to scheme users and providing regular training on maintenance checklist. It is also recommended for engineering and socio-economic researchers to conduct research collaboratively to assess the gap frequently for other kebele pump user and technical performance evaluation for pump that have problems.